Applying Poetic Features to the Teaching of Animal Fantasy Stories in Primary - Duc Khuong, Nguyen (VNU Journal of Science: Education Research; Vol 42 No 2, 2026)
Animal fantasy stories constitute a children’s literary genre rich in aesthetic and educational values, constructed through the personification of animals and objects in order to reflect the human world in ways appropriate to children’s modes of reception. Approaching this genre from a poetics-based perspective, the article clarifies its fundamental poetic characteristics, including imaginative plot structures, systems of personified characters, flexible narrative voice and focalization, the artistic organization of space and time, expressive language, and aesthetic functions. On this basis, the article proposes six pedagogical measures for applying these poetic characteristics to the teaching of reading comprehension of animal fantasy stories in Vietnamese at the primary level. These measures aim to help students engage with texts as integrated artistic wholes, develop reading comprehension competence, aesthetic appreciation, and expressive ability in Vietnamese, thereby enhancing the effectiveness of literature teaching in accordance with the competency-based orientation of the 2018 General Education Curriculum.